Hepatitis, rhabdomyolysis and multi-organ failure resulting from statin use - Rajaram, Muthuram (BMJ Publishing Group, 2009)
OBJECTIVE: To report a case of hepatitis, rhabdomyolysis and multi-organ failure resulting from the use of statins. CASE SUMMARY: A 70 year old Caucasian woman was admitted with general malaise, myalgia and jaundice. She was being treated with a statin for aortic stenosis, the dose of which had been increased approximately 6 months earlier. Investigations showed evidence of hepatitis and rhabdomyolysis resulting in multi-organ failure, eventually leading to her death. DISCUSSION: Statins are inhibitors of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase and are commonly used for treatment of hypercholesterolaemia. The use of high dose statin is becoming increasingly common with emerging evidence suggesting improved outcomes in various conditions. Statins have transformed the care of patients with vascular disease. Statins generally have an excellent safety profile and low risk of adverse reactions, but cases of rhabdomyolysis and hepatitis resulting from their use have been reported. CONCLUSION: While there is good evidence suggesting improved outcomes with use of high dose statins, the potential drug interactions and adverse effects need close attention. All patients started on statin therapy should be counselled regarding the signs and symptoms of muscle injury, particularly those who are on drugs that may have an interaction. In this patient the Naranjo probability scale revealed a probable adverse reaction associated with atorvastatin therapy.